Influence of the Strain Rate on the Notch Toughness of Cold-Forming Steels - Michel, Jan; Bursak, Marian (Communications - Scientific letters of the University of Zilina, 2004)
The paper analyses the influence of the strain rate with loading rates of 1.7.105 4.8 m.s1 on the notch toughness of hot-rolled microalloyed steels S 315 MC and S 460 MC and cold-rolled deep-drawing steels DC 06, H 220 B and H 220 P. It discusses a possibility of utilising a modified notched-bar impact test to predict the formability of these steels at high strain rates of thin steel sheets.